Organizational Identity and Organizational Identification: Degree and Relationship: A Field Study on Academic Staff Members at Mu’tah University - Azab, Husein; Al Tarawneh, Amal (Jordan Journal of Business Administration, 2019)
The aim of this study is to identify the concepts of organizational identity and organizational identification and their relationship, as well as the impact of personal and functional factors, such as sex, age, academic rank and duration of work in the academic field, at Mu’tah University in Jordan. In order to achieve the study objectives, the researchers used primary data from the study’s respondents through distributing a questionnaire to a stratified random sample selected from a population of (248) faculty members at Mu’tah University. The study employed the analytical descriptive method and appropriate statistical methods were used to test the hypotheses of the study. The study reached a number of results, the most important of which are that the level of organizational identification among faculty members at Mu’tah University was high and that the level of organizational identity was moderate. The results also showed a statistically significant relationship between organizational symmetry and organizational identity among faculty members at Mu’tah University, as well as the absence of statistically significant differences in the levels of organizational identification and organizational identity due to personal and functional factors, including gender, age, academic rank and duration of work in the academic field at the University. The study recommended to identify the desires and needs of faculty members at Mu’tah University in order to increase their level of identification with the university, as well as to pay attention to organizational identity and provide the necessary development requirements.